Modification of porous polyethylene scaffolds for cell attachment and proliferation - Sengupta, P.; Surwase, S. S.; Prasad, B. L. (International journal of nanomedicine, 2018)
Synthetic polymers are widely researched for their use in tissue engineering. Control in size, surface area, pore size, and elasticity are the biggest advantages of using a man-made polymer. However, often the polymers are hydrophobic (do not encourage cell attachment); hence, it is hugely challenging to integrate them with the normal tissues. Herein, we have tried to overcome this disadvantage of polymers by coating them with citrate-stabilized gold nanoparticles and arginine. High-density polyethylene, upon multiple treatments, shows low water contact angle, which encourages cell attachment and proliferation in comparison to the untreated polymers.